Preparation of Yb2O3 submicron- and nano-materials via electrospinning. Issue 9 (November 2015) - Henriques, M.S.; Ferreira, A.C.; Cruz, A.; Ferreira, L.M.; Branco, J.B.; Brázda, P.; Jurek, K.; Stora, T.; Gonçalves, A.P.
Abstract: Yb2 O3 nano- and submicron-materials were prepared via electrospinning an homogeneous solution obtained by mixing ytterbium acetylacetonate with cellulose acetate in 1:1 acetyl acetone (2, 4-pentanodione) and glacial acetic acid, followed by heat treatments for 2 h in air atmosphere at temperatures from 550 °C to 850 °C. The electrospinning procedure was carried out at 15 kV, with a tip to collector distance of 10 cm. Thermogravimetric analysis of the electrospun materials indicates their complete decomposition and oxidation below 425 °C, with a total weight loss of 92%. The Williamson–Hall and the Brunauer−Emmett−Teller methods, and scanning and transmission electron microscopy observations were used to characterize the grain size and morphology of the samples. An initial very small grain size (<100 nm) and high porosity were observed in the samples treated at 550 °C, which is related to the important total weight loss. Further heat treatments at higher temperatures lead to the grain growth and agglomeration, increasing the average size to submicron dimensions. Due to their easy grain size tuning, these materials are particularly suitable for applications in fiber amplifiers, fiber optic technologies and lasers.